1975
DOI: 10.1104/pp.55.3.542
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lanthanum on Ion Absorption in Corn Roots

Abstract: Short term (10 min) influx of "6Rb-labeled potassium into corn (Zea mays L. WF9 X M14) root segments was inhibited by La (NO3) (3,12,14,19,20,27,32,35, 41), it forms deposits (above pH 7.2) which can be viewed with the electron microscope, and it has chemical properties resembling those of Ca2. Because of this, La+ has been used to define extracellular space in both animals (12,19,20,32) and plants (3,14,27,35, 41), as well as to study the role of Ca2+ in a number of animal (13,19,34,38) and plant (18,29,30,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…An observed increase of P in maize roots and a relative decrease in shoots was also observed by Diatloff et al (2008), in treatments with relatively low Ce concentrations in nutrient solutions. However, in the same experiment, the P status was not affected in mungbean, which could be due to a lower demand for P. Nagahashi et al (1974) and Leonard et al (1975), hypothesised a non-metabolic apoplastic precipitation of La with P in roots and suggested that this is the reason why La does not cross the endodermis. However, our data suggest that Ce precipitation can also occur not just in the apoplast, but probably also inside the cells, because we desorbed the roots in appropriate cleansing solution and we tested the plants in a P-free nutrient solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An observed increase of P in maize roots and a relative decrease in shoots was also observed by Diatloff et al (2008), in treatments with relatively low Ce concentrations in nutrient solutions. However, in the same experiment, the P status was not affected in mungbean, which could be due to a lower demand for P. Nagahashi et al (1974) and Leonard et al (1975), hypothesised a non-metabolic apoplastic precipitation of La with P in roots and suggested that this is the reason why La does not cross the endodermis. However, our data suggest that Ce precipitation can also occur not just in the apoplast, but probably also inside the cells, because we desorbed the roots in appropriate cleansing solution and we tested the plants in a P-free nutrient solution.…”
Section: Discussionmentioning
confidence: 99%
“…P will precipitate Ce even in the solution, as demonstrated by our observation that the EC 50 for root growth in a complete half-strength Hoagland's is N640 μM, in comparison with 4.2 μM in a half-strength Hoagland's without P and Fe-EDTA. Thus the contrasting observations by Nagahashi et al (1974) and Leonard et al (1975) could simply be due to presence of P (0.25 mM) in the test solutions, so there was no chance for La to enter the root cells, let alone to pass the endodermis. However, further confirmation would be required with TEM-EDAX analysis to see if there are any CePO 4 precipitates inside root cells.…”
Section: Discussionmentioning
confidence: 99%
“…9) indicates that the net transport of Ca2+ is small relative to Ca2+/Ca2+ exchange. (3,18) and animals (2). K+ was less effective in replacing surface-bound Ca24, as indicated by the total 'Ca2+ and the difference between water and CaCl2 at 10-min values.…”
mentioning
confidence: 99%
“…Leonard et al (20) found La`as well as Ca2+ to produce the initial inhibition and later promotion of K+(86Rb) influx, but unlike Elzam and Hodges (8) found competitive kinetics over the first 10 min of influx. On the basis of the impermeability of L3+, they concluded that the inhibition and later promotion of K+ influx arise from reaction of Ca2+ and La3+ in the apoplast, including the external surface of the plasmalemma.…”
mentioning
confidence: 99%